THE EFFECTIVENESS OF HAJJ RITUAL GUIDANCE SERVICES BY THE MINISTRY OF RELIGIOUS AFFAIRS ON EASTERN INDONESIA - St. Arafah (Al-Qalam, 2020)
The main goal to pilgrimage is to achieve the predicate haji mabrur (a pilgrim that completely undergoes the rituals and principles) through its rituals. The Ministry of Religion, specifically the Office of Religious Affairs as the vanguard, has duties and fuctions one of which is to provide Hajj ritual guidance services to prospective pilgrims. This study aimed to determine the level of effectiveness of Hajj ritual guidance services at the Ministry of Religion in Eastern Indonesia, by measuring four dimensions broken down into six indicators namely managerial (committee and supervisor), management (planning and implementation), programs (ritual guidance material) hajj), and facilities and infrastructure. This study used quantitative methods, by distributing questionnaires to 900 respondents in 14 cities in Eastern Indonesia, using the Slovin formula with an estimated error of 0.03. The selection of cities was carried out randomly including Balikpapan, Tarakan, Makassar, Palopo, Parepare, Ternate, Tidore, Gorontalo, Kotamubagu, Kendari, Bau-Bau, Ambon, Tual, and Jayapura. Quantitative data analysis used the liker scale (1-4), and the data were analyzed descriptively. The results showed that the effectiveness of the pilgrimage guidance services at the Ministry of Religion in Eastern Indonesia with a total index was; 3.55 or categorized as "very effective", which were committee indicators (3.54) supervisors (3.47), (3.27) entire planning (3.32), services (3.26), program indicators / guidance materials (3.37), and indicators of facilities and infrastructure (3.34). Hajj ritual services at the Ministry of Religion need to be conducted sustainably through practices for all prospective pilgrims. In addition, The instructor  need to be trained better to improve in the mastery of the Hajj rituals, as well as the maintenance of regulations and facilities and infrastructure required in the Hajj ritual services.